P-099 Sex-Based Differences in Adverse Events of Crohn's Disease Patients Treated with Certolizumab Pegol: A Pooled Safety Analysis of 15 Studies. (March 2016) - Kane, Sunanda; Loftus, Edward; Choudhary, Cuckoo; Randall, Charles; Ali, Tauseef; Kosutic, Gordana; Hasan, Iram; Coarse, Jason; Spearman, Marshall; Regueiro, Miguel
Abstract : Background: The safety of tumor necrosis factor-alpha (TNFalpha) antagonists may be affected by various factors, including sex. 1 The aim of this pooled analysis was to evaluate the safety profile of certolizumab pegol (CZP; a pegylated Fc-free anti-TNF in females (F) versus males (M) with Crohn's disease (CD). Methods: A pooled safety analysis was performed on 15 randomized, placebo (PBO)-controlled (PC), non-PC controlled, and open-label studies of CZP for the treatment of CD. Data were divided into 2 groups and stratified by gender: a PC group (included a CZP arm [total exposure, F = 160.5 versus M = 138.2 patient-years] and a PBO arm [total exposure, F = 139.4 versus M = 122.3 patient-years]), and a CZP All Studies group (included all CZP-exposed patients [total exposure, F = 2314.9 versus M = 2063.2 patient-years]). Treatment-emergent serious adverse events were summarized descriptively, and incidence rates (IR) and 95% confidence intervals (CIs) per 100 patient-years were calculated. Results: At baseline, the prevalence of F was higher across all groups (PC: CZP, F = 483 versus M = 436; PBO, F = 476 versus M = 399; CZP All Studies: F = 1436 versus M = 1134). The mean Crohn's Disease Activity Index was comparable between F versus M (277–288 versus 275–292), as was mean age (both 36–38 years). The proportion of F versus M with serious adverse events was similar in both the PC group (CZP, 9.3% versus 9.9%; PBO, 6.5% versus 7.5%) and the CZP All Studies group (both 33.2%). The IR of serious infections in F versus M were similar in the PC group (CZP: IR, 7.57 [95% CI, 3.91–13.21] versus 9.56 [95% CI, 5.09–16.35]; PBO: 5.08 [95% CI, 2.04–10.47] versus 5.80 [95% CI, 2.33–11.94]) and in the CZP All Studies group (IR, 7.14 [95% CI, 6.06–8.36] versus 5.74 [95% CI, 4.73–6.90]). In the CZP All Studies group, tuberculosis was reported in 6 F versus 4 M. The IR of neoplasms (benign, malignant, and unspecified) was comparable between F versus M in both the PC group (CZP: IR, 0.62 [95% CI, 0.02–3.48] versus 0.72 [95% CI, 0.02–4.03]; PBO: 1.44 [95% CI, 0.17–5.20] versus 0.00) and the CZP All Studies group (IR, 0.74 [95% CI, 0.43–1.19] versus 1.02 [95% CI, 0.63–1.56]). Sex differences were minor with regard to serious cardiac disorders in both the PC group (CZP: IR, 0.62 [95% CI, 0.02–3.48] versus 0.00; PBO: 0.72 [95% CI, 0.02–4.00] versus 0.00 for F versus M) and the CZP All Studies group (IR, 0.17 [95% CI, 0.05–0.44] versus 0.05 [95% CI, 0.00–0.27] for F versus M). Psoriatic conditions were reported in none of the females versus 2 males (IR, 0.10 [95% CI, 0.01–0.35]) in the CZP All Studies group. Conclusions: These findings from a pooled safety analysis of 15 studies did not indicate that there were considerable sex differences with regard to the safety profile of CD patients treated with CZP.